Instrumento de avaliação fonológica: validação de conteúdo - Savoldi, Angélica (2012)
In the pediatric population, the speech disorder is one of the most frequent changes that involve human communication disorders. But, in this area, there is a significant shortage of formal and objective instruments available and suitable to evaluate and diagnose. The goals of an evaluation process just can be achieved when adequate tools and procedures are used. Thus, this study aims to validate an instrument of phonological assessment. In the first stage, a list of words was created, through vocabulary lists child and phonological assessment instruments most commonly used in PB. This list of 722 words was sent to 11 expert judges - three clinical speech therapists, five doctors in speech therapy and three doctors in linguistics that through chosen analysis and criteria, was possible to indicate the most appropriate words to compose the phonological assessment instrument. From these results, was calculated the Kappa agreement obtained between the groups of expert judges and created a new list of words with the most suitable ones. As a result of the previous step, 316 words were shown to be judged by not expert judges. These judges were 72 children, male and female, by public and private schools, aged between 3:0 and 8:11 years. They rated the word by familiarity and naming of the illustration. Words with highest number of correct naming were reanalyzed as theoretical-linguistic another list of words was created with 193 considered best words to make the instrument of child s phonological assessment.